Związek zaburzeń lękowych z percepcją bodźców zagrażających = The relation between anxiety disorders and perception of threatening stimuli - Florkowski, Marcin (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article has reviewed the research done on the relationship between anxiety and perception of threatening stimuli. The results of experimental studies are inconsistent: studies based on and inspired by the psychoanalytic theory suggest that anxiety disorders are revealed in form of changes such as higher perception of stimuli, selective ignorance of threatening stimuli, etc.
Keywords: percepcja; percepcja selektywna; lęk; obronność percepcyjna; uwaga; wyparcie; mechanizmy obronne; perception; selective perception; anxiety; perceptual defense; attention; repression; defense mechanisms